Financial Performance Analysis in Government Langkat Regency - Lestari, Putri Dwi; Tripriyono, Agus (International Journal of Integrative Sciences, 2024)
This study aims to analyze the financial performance of the Langkat Regency Government from 2018 to 2022 using several relevant financial ratios. The ratios that will be used include the Decentralization Degree Ratio, Regional Financial Independence Ratio, PAD (Regional Original Income) Effectiveness Ratio, and Expenditure Efficiency Ratio. The method used in this study is quantitative research with a descriptive approach. This means that the study will rely on secondary data in the form of budget realization reports from the Langkat Regency Government for the 2018-2022 period. The data analysis technique used is quantitative descriptive, which will help describe and analyze financial performance based on the ratios that have been mentioned. The results of this study indicate that the average value is 6.9% where the Decentralization Degree Ratio of the Langkat Regency Government is in the "very low" criteria, the average value is 8.36%, the Regional Financial Independence Ratio is categorized as "very low", the average value of 100.8% places the PAD Effectiveness Ratio in the "very effective" category and the average value of 89.94%, the Expenditure Efficiency Ratio is classified as "efficient"